2019
DOI: 10.22190/fupes190413034m
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Arthistic Gymnastics Program on Physical Fitness of Adolescents

Abstract: The aim of the research is to determine the effects of the arthistic gymnastics program on the Physical fitness of adolescents. The sample of participants consisted of 28 participants, males, aged 14 years ± 6 months, seventh grade of "Bubanjski Heroji" elementary school in Niš. The sample was divided into two subgroups. The experimental group (EG) consisted of 14 participants who, during the experimental period, realized the program of artistic gymnastics during the main phase of a physical education class, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…The recommendation for the duration of the experimental program of gymnastics and acrobatics with positive effects on the body composition, flexibility and motor fitness is 16 weeks (Rudd, 2016;Paunović, 2018;Miletić et al, 2019), or 12 weeks and more (Akin, 2013;Mićović et al, 2018). The experimental program of acrobatics in this study lasted 16 weeks, after which the results confirmed the positive impact on fitness components and the recommendations of previous research.…”
Section: Discussionsupporting
confidence: 86%
“…The recommendation for the duration of the experimental program of gymnastics and acrobatics with positive effects on the body composition, flexibility and motor fitness is 16 weeks (Rudd, 2016;Paunović, 2018;Miletić et al, 2019), or 12 weeks and more (Akin, 2013;Mićović et al, 2018). The experimental program of acrobatics in this study lasted 16 weeks, after which the results confirmed the positive impact on fitness components and the recommendations of previous research.…”
Section: Discussionsupporting
confidence: 86%
“…The reason for statistically non-significant changes for flexibility (DBV) should be found in insufficient attention to the development of this ability, both by teachers at school and in the structure of training programs for selected sports (Sands, & McNeal, 2000). On the other hand, studies (Paunović, 2018;Miletić et al, 2022) clearly showed the positive effects of physical education classes in combination with sports gymnastics training on the flexibility of elementary school students.…”
Section: Discussionmentioning
confidence: 99%
“…after 12 weeks. Measurements were carried out during regular physical education classes, using standardized measuring instruments with satisfactory metric characteristics (Findak et al, 1996;Paunović, 2018;Miletić, 2022). The measurement was carried out by expert and trained meriocims, physical education professors and students of doctoral academic studies.…”
Section: Methodsmentioning
confidence: 99%